2022
DOI: 10.3389/fmed.2021.798334
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Predisposition to Low-Density Lipoprotein Cholesterol May Increase Risks of Both Individual and Familial Alzheimer's Disease

Abstract: Background: Previous observational studies provided conflicting results on the association between low-density lipoprotein cholesterol (LDL-C) level and the risk of Alzheimer's disease (AD).Objective: We used two-sample Mendelian randomization (MR) study to explore the causal associations between LDL-C level and the risks of individual, paternal, maternal, and family history of AD.Methods: Summary-level genetic data for LDL-C were acquired from results of the UK Biobank GWAS. Corresponding data for paternal, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…While the association between the LDL-PGS and the risk for Alzheimer’s disease was slightly attenuated after removing the ApoE locus (OR = 1.23 vs. 1.36 per SD PGS increase), the association remained significant ( p -value = 2.51 × 10 −21 ). Recent Mendelian randomization studies also provide evidence for the causal effect of lipids on risk for dementia [ 44 ] and Alzheimer’s disease [ 45 ]. The LDL-C and TC PGSs were also associated with increased aspartate aminotransferase levels (a liver enzyme), in accordance with other studies [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…While the association between the LDL-PGS and the risk for Alzheimer’s disease was slightly attenuated after removing the ApoE locus (OR = 1.23 vs. 1.36 per SD PGS increase), the association remained significant ( p -value = 2.51 × 10 −21 ). Recent Mendelian randomization studies also provide evidence for the causal effect of lipids on risk for dementia [ 44 ] and Alzheimer’s disease [ 45 ]. The LDL-C and TC PGSs were also associated with increased aspartate aminotransferase levels (a liver enzyme), in accordance with other studies [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…First, these data adopted to infer the correlation between obesity and HDP risk factors came mainly from European ancestry, therefore, subsequent studies need to test other regions and races to determine whether the correlation is consistent in other populations ( 24 ). Second, we are not able to further explore subgroup analysis on the interest covariates because we just adopted the summary data rather than individual patient data ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study also demonstrated that total cholesterol levels decreased in AD patients but remained stable in healthy people (Toro et al., 2014). Studies have also shown that high levels of low‐density lipoprotein cholesterol (LDL‐C) could increase the risk of individual and familial AD (Tan et al., 2021). Hence, it is still worth studying whether a maternal history of AD can affect the cholesterol metabolism of offspring.…”
Section: Introductionmentioning
confidence: 99%